Effect of glazing and polishing on opalescence and fluorescence of dental ceramics - Sedighe Sadat Hashemikamangar; Alireza Mahmoudi Nahavandi; Marzieh Daryadar; Sara Valizadeh; Mutlu Özcan (Wiley, 2022)
Abstract Objective Tooth enamel has opalescence and fluorescence, which should be mimicked by esthetic dental restorations. The purpose of this study was to compare the effects of glazing and polishing on the opalescence and fluorescence of dental ceramics. Materials and Methods Twenty‐four discs were fabricated of feldspathic, IPS e.max, zirconia, and Enamic ceramics with 10 mm diameter and 0.5 and 1 mm thicknesses (n = 12). Of the discs fabricated with 0.5 and 1 mm thicknesses, half of them were glazed and the remaining half were polished (n = 6). Opalescence was calculated as the difference in yellow‐blue (CIE ∆b*) and red‐green (CIE ∆a*) color axes between the transmitted and reflected colors. The fluorescence of specimens was measured by a novel technique. Data were analyzed using two‐way analysis of variance at a 0.05 level of significance. Results In all groups (except for the Enamic ceramic), the mean opalescence of polished specimens (e.max = 2.704, feldspathic = 1.67, zirconia = 3.143) was higher than that of glazed specimens (e.max = 2.163, feldspathic = 1.016, zirconia = 2.690). The mean opalescence of glazed Enamic specimens (2.140) was higher than that of polished specimens (1.308). The fluorescence of glazed and polished specimens was not significantly different. Conclusion Surface treatment (glazing/polishing) affects the opalescence, but not the fluorescence of dental ceramics evaluated in this study.